Sistem Registrasi Pasien Pada Apotik Cahaya Medika Bireuen Berbasis Web - T Irfan Fajri, Novia Hasdyna (LPPM-UNIKI, 2023)
Currently, the Cahaya Medika Bireuen Pharmacy does not yet have an online-based queuing system that makes it easier for prospective patients to take a queue number without having to go to the pharmacy to take a queue number. This study aims to implement a web-based information system that can improve patient care. The system built does not only focus on taking queue numbers. The results of this study also include information about facilities and doctors' schedules, making it easier for the public to find information about clinics.